Superconductivity without dependence on valence electron density in (Al, Zn, Co) doped YBCO systems - Yufeng, Z.; Dandan, W.; Pinglin, L. (Физика низких температур, 2010)
We adopted the x-ray diffraction, oxygen contents, positron annihilation technology and simulation methods to investigate systematically YBa₂Cu₃–x(Al,Zn,Co)xO₇–δ (x = 0–0.5) cuprates. The experimental results and simulated calculations support the existence of cluster effect. Moreover, it is concluded that the cluster effect is an important factor on suppression of the superconductivity and the Tc does not depend directly on the density of valence electron in the samples.